The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jonm.12539
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing the patient-centred innovation questionnaire for hospital nurses

Abstract: Patient-centred innovation questionnaire could give a measure for evaluating the implementation of patient-centred care and could be used as a management tool during the process of nurse innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…To the best of our knowledge, this is the first systematic scoping review dimensions related to all of the concepts of patient engagement. 27,30,36,37 Furthermore, we found that no tool simultaneously assesses the core dimensions of the partnership in care presented in our conceptual framework (individualized care, empathy, interpersonal trust, communication, experiential knowledge and self-care). 7 Tools assessing preferences regarding patient engagement in care are relatively scarce.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first systematic scoping review dimensions related to all of the concepts of patient engagement. 27,30,36,37 Furthermore, we found that no tool simultaneously assesses the core dimensions of the partnership in care presented in our conceptual framework (individualized care, empathy, interpersonal trust, communication, experiential knowledge and self-care). 7 Tools assessing preferences regarding patient engagement in care are relatively scarce.…”
Section: Discussionmentioning
confidence: 88%
“…We categorized the dimensions assessed in each tool into the main concepts of engagement, which include patient centredness, empowerment and shared decision‐making. The results reveal that the two main concepts evaluated in the included scales are shared decision‐making (81%, n = 13) 24 , 25 , 26 , 27 , 29 , 30 , 32 , 34 , 35 , 36 , 37 , 38 and patient centredness (75%, n = 12), 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 36 , 37 , 38 while empowerment is present in 50% ( n = 8) of the included tools. 27 , 28 , 30 , 33 , 34 , 35 , 36 , 37 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations